Investigating the effect of teacher mediation on student expressed reasoning. Issue 3 (31st May 2019) - Moreira, Patricia; Marzabal, Ainoa; Talanquer, Vicente
Abstract : Understanding how chemistry teachers' interventions shape the reasoning that students express after a lesson is critical to support prospective and in-service teachers as they work with students' ideas in the classroom. In this qualitative research study, we analysed changes in the reasoning expressed by 10th grade students in a Chilean school in their written explanations about freezing point depression before and after a lesson on the topic. We also investigated how the teacher's interventions shaped the type of reasoning expressed by participating students. Our findings revealed significant shifts in the types of explanations generated after the lesson. A significant number of students transitioned from relational to simple causal reasoning in their pre- and post-lesson explanations. After the lesson most of the explanations were based on the activities of one or more of the system's entities. Analysis of teacher–student interactions during the observed lesson suggests that the teacher's mediation played a central role in the shift towards simple causal reasoning with centralized causality that was observed. The teacher in our study was more skilled at eliciting students' ideas than at helping students develop them with proper scaffolding. Thus, the observed classroom talk could not be considered as accountable talk, as most of the key ideas were introduced, selected, or reshaped by the teacher.